Smart Electric Solar Car Application System Based on Android - Ahmad Riyadi; Haryanto; Koko Joni; Achmad Ubaidillah (Universitas Muhammadiyah Sidoarjo, 2021)
Electronic devices that are increasingly developing make alternatives to human activities every day so that human work can be completed easily. Like smartphones as electronic devices that have dominated electronic devices so that users have the convenience of fulfilling their needs. There have been many electronic devices that can be controlled by simply pressing the remote button without even touching anything but by voice commands. Technology has developed rapidly so that a microcontroller like Arduino can be integrated with other devices, such as an electric car that is equipped with solar panels as a source of electrical energy and controlled via an Android smartphone. In this study, an electric car will be controlled by an application on a smartphone with voice commands, and using bluetooth as a connection between the application system and the electric car system.